Nostalgie dell’oikos. Sui margini dell’abitare - Tesorone, Fabio (Mechane, 2023)
The “housing crisis” appears to be endemic in the Western world. However, our collective consciousness seems to be preoccupied with the “metaphysical” threats to the home rather than focusing on the material conditions of access to housing. The “stranger”, who invades the “native home”, as well as technology that disarticulates the semantics of distance and proximity, inside and outside, promotes nationalist nostalgia for Heimkunft (“coming to home”). Thus, nostalgia for a lost oikos has to be thought as part of our way of thinking about dwelling. In W. Benjamin’s Passages, we will show how the bourgeois model is formed through the aestheticization of the archaic, as well as nostalgia for the feudal system. The analysis of M. Heidegger’s famous essay Building Dwelling Thinking, on the other hand, will allow us to investigate the relationship between the concept of dwelling and an agro-ecological model. Finally, we will show how this notion of dwelling supports nationalist rhetoric about the “native home” through Jacques Derrida’s analysis of a selection of Heidegger’s texts on poetry.